Métricas de SST e dimensões de desempenho organizacional: evidências de relações em um caso da indústria de transformação. - Barros, Adriano David Monteiro de (2015)
This paper proposes an analysis of the relations between the Security metrics and Labour Health and organizational performance dimensions. This research considered the premise that the Safety and Occupational Health directly influences the overall performance of the company, since as an integrated subsystem to the global system, this may or may not promote improvements in performance, according to the strategies defined by the organization. Based on the literature, we have identified limitations in regard to searches related to this context, as well as the need to evaluate and measure the performance of the company using SST relationship between size and performance. Subsequently, we analyzed different existing performance measurement models and it was observed that most used as performance criteria Productivity, Quality, Flexibility and Cost, as important elements for the competitiveness of the market. Then we conducted a case study on a manufacturing industry in order to check which had relations between security metrics and dimensions of organizational performance proposed by the company. In the case study they were conducted structured interviews with employees of the company directly linked to the Occupational Safety area. From the case study, it was concluded that there is an increasing need, to integrate the area of SST to other sectors of the company, so that it can measure its real influence on organizational performance. We found that not all SST metrics are directly related to organizational performance dimensions. Productivity and Flexibility are those with the highest degree of relationship between the metrics, the company said.